Heterodimeric Fc-fused IL12 shows potent antitumor activity by generating memory CD8+ T cells - Jung, Keunok; Ha, Ji Hee; Kim, Jung Eun; Kim, Jeong Ah; Kim, Ye Jin; Kim, Chul Ho; Kim, Yong Sung (OncoImmunology, 2018)
Interleukin-12 (IL12) (p35/p40 complex) is a heterodimeric cytokine with potent anti-tumor activity. However, its short serum half-life and high dose-related toxicities limit its clinical efficacy. Here, we constructed heterodimeric immunoglobulin Fc-fused mouse IL12 (mIL12) in a monovalent binding format (mono-mIL12-Fc) to generate long-acting mIL12 in the naturally occurring heterodimeric form. Mono-mIL12-Fc exhibited a much longer plasma half-life than recombinant mIL12, enabling twice-weekly systemic injections to remove established tumors in syngeneic mouse models. Mono-mIL12-Fc was more potent than wild-type Fc-based bivalent-binding IL12-Fc (bi-mIL12-Fc) for eradicating large established immunogenic tumors without noticeable toxicities by enhancing interferon-γ production and the proliferation of immune effector cells in tumors. More importantly, mono-mIL12-Fc triggered weaker IL12 signaling than bi-mIL12-Fc, favoring the generation of functional and protective memory CD8+ T cells. Our results demonstrate that heterodimeric-Fc-fused IL12 is a suitable format for augmenting adaptive CD8+ T cell immune responses, providing a practical alternative to the systemic administration of IL12 for antitumor therapy.
Keywords: anti-tumor therapy; Immunoglobulin heterodimeric Fc; Inflammation and cancer; Interleukin 12; large established immunogenic tumors; memory CD8+ T cells; Models of immunostimulation; monovalent binding format; Therapeutic antibodies